The coronal line region of active galactic nuclei - Rodríguez-Ardila, Alberto; Cerqueira-Campos, Fernando (Frontiers in Astronomy and Space Sciences, 2025)
Forbidden coronal lines has traditionally called the attention due to the high-energy photons required for their production (IP >100 eV, where IP is the ionisation potential of the transitions that originate the line). As such, they are regarded as the most highly ionised component of Active Galactic Nuclei (AGN). For decades, it was thought that they were only formed in the inner portions of the narrow line region (NLR). Nowadays, due to the larger sensitivity of the detectors and the availability of integral field unit (IFU) spectrographs, that emission in addition to the nuclear component is found to be extended up to a few kiloparsecs away from the active centre. In this review, we highlight the most important aspects of the coronal emission and discuss the recent developments in the field. In particular, we emphasize the discovery that they can be used to determine the mass of the central supermassive black hole, to reconstruct the SED, as well as to trace the most energetic feedback component of the ionised gas in AGN.